Relationship between advanced lung cancer inflammation index and long-term all-cause, cardiovascular, and cancer mortality among type 2 diabetes mellitus patients: NHANES, 1999–2018 - Chen, Yaying; Guan, Mengqian; Wang, Ruiqi; Wang, Xuewen (Frontiers in Endocrinology, 2023)
Background: Type 2 diabetes mellitus (T2DM) was a major global health threat. As a chronic low-grade inflammatory disease, the prognosis of diabetes was associated with inflammation. The advanced lung cancer inflammation index (ALI) served as a comprehensive index to assess inflammation. This study aimed to estimate the association between ALI and all-cause, cardiovascular disease (CVD), and cancer mortality in T2DM patients. Methods: We extracted cohort data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999-2018 for analysis. The weighted Kaplan-Meier analysis and multivariate-adjusted Cox analysis were utilized to evaluate the relationship between ALI and all-cause, CVD, and cancer mortality in T2DM patients. Restricted cubic spline (RCS) analysis was employed to assess their non-linear relationship. Stratified analysis and interaction analysis were conducted to enhance the robustness of the results. Results: The study incorporated a total of 3,888 patients. An increase in ALI was associated with a reduced risk of all-cause and CVD mortality in T2DM patients, but not related to cancer mortality. There were J-shaped and L-shaped non-linear relationships between ALI and all-cause, CVD mortality in T2DM patients, respectively. The inflection points were 90.20 and 93.06, respectively. For values below the inflection point, every 10U increase in ALI, both all-cause and CVD mortality risk decreased by 9%. Beyond the inflection point, all-cause mortality rose by 3%, while CVD mortality remained unaffected. Gender-stratified RCS analysis indicated a linear negative relationship between CVD mortality and ALI in female T2DM patients, whereas the trend in males aligned with the overall population. Conclusion: Our research initially identified a significant correlation between increased ALI levels with decreased all-cause and CVD mortality in T2DM patients. There were J-shaped and L-shaped non-linear relationships between ALI and all-cause, CVD mortality in T2DM patients, respectively. For female patients, there was a linear negative relation between CVD mortality and ALI, whereas the trend in males aligned with the overall population. These findings suggested that maintaining ALI (for example, control body weight and keep albumin in the normal range) within a certain range in the clinical settings was crucial for improving all-cause and CVD mortality in T2DM patients.